DEFEATING COMMUNIST INSURGENCY - Van Heerden, K.W.J. (Scientia Militaria - South African Journal of Military Studies, 2011)
This book was written approximately 16 years ago and much of it is based on the experiences of the author obtained during the insurgencies in Malaya and Vietnam. The book is a study of the basic theories of communist insurgency and of counter insurgency as they operate on the ground and affect the population of a threatened country. Much of what is propagated in this book have been experienced by the SADF during its struggle against insurgency. Some of the systems used in Malaya and Vietnam was also used in Rhodesia during their war. Some of the systems propagated eg Strategic Hamlets, although effective in Malaya, had still to be proven in Vietnam! The following is a summary of some of the subjects mentioned in the book which has a relation to our own war and which has already been implemented or could still be implemented.